Early prognosis of multiple sclerosis - Swanton, Josephine; Fernando, Kryshani; Miller, David (Handbook of Clinical Neurology, 2014)
Establishing the prognosis for multiple sclerosis (MS) early in the disease course is critically important for patients who develop this disease. Potentially, this information could be used to guide the selection of which disease modifying therapy (if any) should be started in which individual and to determine, over course of the illness, when the therapeutic approach needs to be modified. Regardless, of its importance, however, we only have a limited ability to predict how an individual’s illness will evolve. For several decades, we have known about certain clinical features of MS that seem to associated with a more benign course (e.g., female gender, clinical onset before the age of 40 years, few early relapses, slow early accumulation of fixed deficits, and the initial involvement of only sensory systems). Nevertheless, the prognostic value of these clinical features offer only limited help to individual patients in making their different (and difficult) life-choices. For this reason, there have been numerous attempts to develop paraclinical tests, which can augment (and improve upon) this clinical prognostic information. These approaches have included the use of magnetic resonance imaging (MRI) measures such as gadolinium enhancement, new T2 lesions, the volume of T2 lesion burden, brain atrophy (either whole brain or separately for grey and white matter), spinal cord atrophy, cortical connectivity, and determining the characteristics and chemical composition of the normal appearing white matter. They have also included investigations of the use of immunological markers for establishing prognosis. Nevertheless, this field is still only in its infancy and our ability to predict accurately the outlook for an individual remains limited at best. This chapter reviews the current evidence, taken from both clinical and paraclinical sources, as it relates to establishing this prognosis and provides insight to where, in the future, we need to look.